2021
DOI: 10.1186/s43251-021-00041-y
|View full text |Cite
|
Sign up to set email alerts
|

Incremental dynamic analysis of the long-span continuous beam bridge considering the fluctuating frictional force of rubber bearing

Abstract: In the seismic design of long-span bridges, the classic bi-linear model was used to simulate the frictional restoring force of the rubber bearings. However, in actual earthquake, the rubber bearing suffered fluctuating axial pressure in earthquake, even separated from the beam when vertical component of the earthquake was too strong. Employing the bi-linear model for the bearing may incorrectly estimate the seismic response of the bearings, as well as the whole bridge. This paper developed a nonlinear friction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…During an actual earthquake, the pot bearing may experience axial pressure fluctuations and can separate from the beam if the vertical component of the earthquake is too intense. Using the bilinear model to simulate the friction restoring force of the pot bearing will result in an incorrect estimation of the seismic response of both the bearing and the entire bridge (Liao et al, 2021). In the simulation of the shape memory alloy supplemented with lead rubber bearings (SMA-LRB) hysteretic response, it is found that the bilinear model cannot reflect the actual behavior of the SMA-LRB, which leads to a certain degree of uncertainty in the results (Dezfuli et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…During an actual earthquake, the pot bearing may experience axial pressure fluctuations and can separate from the beam if the vertical component of the earthquake is too intense. Using the bilinear model to simulate the friction restoring force of the pot bearing will result in an incorrect estimation of the seismic response of both the bearing and the entire bridge (Liao et al, 2021). In the simulation of the shape memory alloy supplemented with lead rubber bearings (SMA-LRB) hysteretic response, it is found that the bilinear model cannot reflect the actual behavior of the SMA-LRB, which leads to a certain degree of uncertainty in the results (Dezfuli et al, 2017).…”
Section: Introductionmentioning
confidence: 99%